Análise do Programa de Aquisição de Alimentos-PAA no município de Caxias-MA - Carneiro, Joabe Alves (Universidade Federal de São Carlos, 2019)
The general objective of this dissertation is to analyze the configuration of the dynamics of the economic, social and environmental aspects of the Food Acquisition Program in Caxias, Maranhão state, showing the importance of family farming in local development. According to data from the Brazilian Institute of Geography and Statistics, the municipality has a population of 155,129 inhabitants, 24% of which are in rural areas. The research tool used was qualitative and quantitative, through a case study. 45 Forms with open and closed questions were applied, which were completed by the researcher. The dissertation is organized in (chapter-article) format, structured with general introduction, three article-chapters and general considerations. The second chapter-article was titled “Coverage of the Food Acquisition Program (PAA) in BRAZIL: An Approach from the Analysis of Conab Executive Summaries (2003-2017)”. In this second chapter, it was noticed that in Brazil there was growth and decrease of the financial resources destined to the PAA, besides the disparities in its distribution among the Brazilian regions. In the third chapter entitled “PAA Socioeconomic Profile, Functioning, Marketing and Income: A Case Study in the Municipality of Caxias-Maranhão”, it was observed that among the beneficiaries surveyed 70% are female, 50% are aged between 36 and 49 years, 25% are aged 18-35 and people over 50 also represent 25%. Of the 44 farmers participating in the study, 43% self-described brown, 25% black and 28% self-described as “dark brown”. It was observed that 61% of the sample beneficiaries do not have complete elementary school, those who receive social benefit are 54% and 75% are female. The average amount received per beneficiary was R $ 182.33, the minimum of R $ 77.00 and the maximum of R $ 436.00. The Fourth Chapter, entitled “Agricultural Production Diversification, Farmers' Organization and Environmental Aspects within the PAA in the Municipality of Caxias Maranhão” analyzed that before the PAA farmers produced 11 different types of productive crops and with the arrival of the program this amount went up. to 36. In environmental aspects, it was found that even in the farmers' properties that benefited from rivers, streams, marshes and ponds, some did not conserve them. It was also noticed that the system of consortium between agricultural activities is practiced by 61% of farmers. The use of pesticides in productive areas totaled 63.63%, while 68.18% of farmers use chemical fertilizers. Regarding the knowledge of agroecology, 45.45% of the survey respondents said they were completely unaware of the term and 54.55% knew the term. The holdings of farmers in associations, according to the survey, represent 56.81% and in cooperatives 15.9%. The advantages of participating in the program, according to farmers, were: increased income; self esteem; incentive to cultivate the land; exchange of experiences and others.
Analysis of the PAA Food Acquisition Program in the city of Caxias-MA
Keywords: Agricultura familiar; Diversificação de cultivos; Desenvolvimento local; Agroecologia; Family agriculture; Crop diversification; Local development; Agroecology; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS::ANALISE INSTITUCIONAL